Graphene Bridge Heterostructure Devices for Negative Differential Transconductance Circuit Applications - Lee, Minjong; Kim, Tae Wook; Park, Chang Yong; Lee, Kimoon; Taniguchi, Takashi; Watanabe, Kenji; Kim, Min‑gu; Hwang, Do Kyung; Lee, Young Tack (Nano-Micro Letters, 2022)
Two-dimensional van der Waals (2D vdW) material-based heterostructure devices have been widely studied for high-end electronic applications owing to their heterojunction properties. In this study, we demonstrate graphene (Gr)-bridge heterostructure devices consisting of laterally series-connected ambipolar semiconductor/Gr-bridge/n-type molybdenum disulfide as a channel material for field-effect transistors (FET). Unlike conventional FET operation, our Gr-bridge devices exhibit non-classical transfer characteristics (humped transfer curve), thus possessing a negative differential transconductance. These phenomena are interpreted as the operating behavior in two series-connected FETs, and they result from the gate-tunable contact capacity of the Gr-bridge layer. Multi-value logic inverters and frequency tripler circuits are successfully demonstrated using ambipolar semiconductors with narrow- and wide-bandgap materials as more advanced circuit applications based on non-classical transfer characteristics. Thus, we believe that our innovative and straightforward device structure engineering will be a promising technique for future multi-functional circuit applications of 2D nanoelectronics. Highlights: 1 Graphene (Gr)-bridge heterostructure, consisting of a laterally series-connected (cascade) ambipolar/Gr/n-type 2D van der Waals channel materials for ambipolar semiconductor-based high-end application devices was developed. 2 Non-classical transfer characteristics (humped curve) in FET operation and negative differential transconductances were observed. 3 Gr-bridge heterostructure device with PdSe2 (narrow bandgap) allows multi-value logic operation while WSe2 (wide bandgap) enables frequency tripler circuit operation.